Identifikasi Etnosains Pada Kerajinan Anyaman Okomama Dengan Pewarna Alami Tanaman Nila Di Desa Noesiu - Hilary Fridolin Lipikuni; Ela Mariana Sill (Journal on Education, 2024)
Ethnoscience is an approach to science learning that implements local wisdom (regional culture) using certain cultural products. Local wisdom can be in the form of food and drink, traditional ceremonies, dances, games, traditional language and traditional weaving. One of the traditional woven based local wisdom is okomama. Traditional woven okomomama made from palm leaves using indigo plants as a natural dye for motifs and color patterns. The purpose of this study is to explore physical concepts in the process of okoma weaving. The research method used is qualitative descriptive research in the form of interviews, field observations and documentation. The research data was analyzed in several stages, namely data reduction, display data and conclusions. This study aims to identify physics objects and concepts that can be found in genius-based local science learning. The results of the study obtained that in the process of making natural dyes in ocomoma matting there are physical concepts identified in the concepts of frictional force, material strength, load distribution, pressure, work, energy, temperature, heat, absorption, reflection of light, and change of form.